Stimulasi Nervus Vagus sebagai Terapi Adjuvan pada Anak Epilepsi Resisten Obat : Literature Review - Jonathan Rivaldo Gultom; Roro Rukmi Windi Perdani; Septia Eva Lusina; Intanri Kurniati (Jurnal Anestesi, 2025)
Drug-resistant epilepsy is the failure to administer two or more anti-epileptic drugs to an epileptic child which becomes a challenge in its management. Failure of this therapy can result in a decrease in the child's quality of life, such as decreased cognitive function, personality disorders and sleep quality. This can also have a negative impact on the parents who care for them. Vagus nerve stimulation is a device attached to the child's left chest and neck that can stimulate the vagus nerve. This literature review provides a comprehensive overview of vagus nerve stimulation in the treatment of drug-resistant epilepsy, including a discussion of indications, techniques for use, and scientific evidence for the efficacy of vagus nerve stimulation. We reviewed and analyzed the current scientific evidence to assess the effectiveness of vagus nerve stimulation in the treatment of drug-resistant epilepsy.